Blaga hipotermija in perkutana koronarna intervnecija pri zdravljenju bolnika s predbolnišničnim zastojem srca zaradi akutnega srčnega infarkta - Stojić, Milena (Zdravniški vestnik, 2008)
Background Coronary artery disease is the most common cause of sudden cardiac death. More then 50% of patients die before reaching the hospital and at discharge survival rates remain as low as 5%. High mortality is mainly due to a cardiovascular collapse and ischemic brain injury. According to current guidelines percutaneous coronary intervention (PCI) is a golden standard in treatment of myocardial infarction with ST elevation (STEMI). As for now, the only well-documented therapeutic modality for prevention of ischemic brain injury is mild induced hypothermia (MIH). Methods At Center for Internal Intensive Medicine (KOIIM) both procedures (MIH and PCI) are being combined incomatose survivors in whom STEMI is likely since late 2003. Results We report on a 48-year old male who suffered out-of-hospital cardiac arrest one hour after onset of chest pain. Bystander basic life support was not provided.On arrival of prehospital emergency medical team ventricular fibrillation (VF) was documented. Following chest compression and defibrillation spontaneous circulation was established. 12-lead EKG revealed STEMI. Since patient remained comatose despite successful re-establishment of spontaneous circulation MIH was immediately started. Upon hospital admission urgent coronary angiography and successful primary percutaneous intervention were performed. Because of impending cardiogenic shock intra-aortic balloon pump was inserted. Hypothermia with target body temperature between 32 and 34 degrees C was maintained for 24 hours. Standard intensive care procedures wereemployed. The patient survived hospital discharge without any neurologicaldeficit and lives normal life without any symptoms of left ventricular dysfunction for more than 250 days. Discussion Early aggressive and combined treatment of comatose survivors with sudden cardiac arrest due toSTEMI proves to be safe, feasible and efficient in preventing neurological damage.
Keywords: Angioplastika transluminalna, perkutana, koronarna; Angioplasty, Transluminal, Percutaneous Coronary; cardiovascular disease; Coronary Arteriosclerosis; Heart Arrest; hipotermija; kardiovaskularne bolezni; Koronarna arterioskleroza; Middle Age; Miokardni infarkt; Myocardial Infarction; Srce, zastoj; srčni infarkt; srčni zastoj; Srednja leta; therapy; Treatment Outcome; zdravljenje; Zdravljenje, izid